The relationship with disease severity of ischemia-modified albumin levels in diabetic nephropathy (Annals of Medical Research, 2023)
Aim: While type 2 diabetes (T2DM) is increasing rapidly, developing diabetic complications are the leading cause of morbidity and mortality. Biochemical markers are important for early diagnosis and treatment of nephropathy, which is a common complication. The aim of this study is to evaluate serum ischemia-modified albumin (IMA) levels in the development of diabetic nephropathy in T2DM patients and to determine the effectiveness of this parameter in predicting the presence and severity of nephropathy.Materials and Methods: 68 adult patients diagnosed with T2DM and 30 healthy controls were included in this study. The T2DM group consisted of 34 patients without microalbuminuria (
Keywords: Ischemia-modified albumin; Microalbumin; Diabetic nephropathy; Albumin/creatinine ratio